2018
DOI: 10.1097/txd.0000000000000819
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of a Tofacitinib-based Immunosuppressive Regimen After Kidney Transplantation: Results From a Long-term Extension Trial

Abstract: BackgroundTofacitinib is an oral Janus kinase inhibitor. This open-label, long-term extension (LTE) study (NCT00658359) evaluated long-term tofacitinib treatment in stable kidney transplant recipients (n = 178) posttransplant.MethodsPatients who completed 12 months of cyclosporine (CsA) or tofacitinib treatment in the phase IIb parent study (NCT00483756) were enrolled into this LTE study, evaluating long-term tofacitinib treatment over months 12 to 72 posttransplant. Patients were analyzed by tofacitinib less-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…As standalone immunosuppressant Tofa demonstrated great inhibitory capacity, 28,29 but safety concerns deriving from its long-term administration paused its further clinical investigation in transplantation. [67][68][69] We propose a different utilization of Tofa: short-term administration intervals that parallel the infusion of CTLA4-Ig. This regimen would be more cost-effective than the combination of CTLA4-Ig with biologics like complement inhibitors 23,70 or blocking antibodies, 22,41 while preserving similar efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As standalone immunosuppressant Tofa demonstrated great inhibitory capacity, 28,29 but safety concerns deriving from its long-term administration paused its further clinical investigation in transplantation. [67][68][69] We propose a different utilization of Tofa: short-term administration intervals that parallel the infusion of CTLA4-Ig. This regimen would be more cost-effective than the combination of CTLA4-Ig with biologics like complement inhibitors 23,70 or blocking antibodies, 22,41 while preserving similar efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the reported rapid normalization of blood parameters after treatment termination, 71 and the quick reversibility of inhibition of DC phenotype we reported, indicate that Tofa allows great flexibility in patient management. [67][68][69] With further elucidation of the mechanisms underlying the synergism between Tofa and CTLA4-Ig and with optimization of the administration protocol, e.g. by implementing a localized delivery of Tofa (a strategy we are currently exploring), 72 we believe there is great potential for designing safer and highly effective strategies for management of transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…In some patients with inherited autoinflammatory disease, the doses required to control symptoms were high, and treatment was associated with BK viremia (83). A third consideration is that in some settings multiple immunosuppressive drugs are used, thus increasing the incidence of infection (84). In transplant trials, tofacitinb was found effective compared with cyclosporin A; however, these patients were also treated with mycophenolate and steroids.…”
Section: Side Effects Of First-generation Jakinibsmentioning
confidence: 99%
“…In transplant trials, tofacitinb was found effective compared with cyclosporin A; however, these patients were also treated with mycophenolate and steroids. Perhaps unsurprisingly, there was a higher incidence of infections and some patients developed posttransplant Epstein-Barr virus-related lymphoproliferative disease (84).…”
Section: Side Effects Of First-generation Jakinibsmentioning
confidence: 99%
“…[ 26 ] Tofacitinib has shown promising antirejection efficacy in nonhuman primate transplant models and in humans receiving kidney transplantation. [ 27–29 ] Unpublished data from our lab suggest that a combination therapy of tofacitinib delivered via repeated oral gavages synergizes with CTLA4‐Ig to enhance the survival of mice receiving heterotopic heart transplants. Although promising, systemic and prolonged administration of tofacitinib can be problematic.…”
Section: Introductionmentioning
confidence: 99%